2006
DOI: 10.1021/la0600245
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controlled Synthesis of Monodispersed Silver Nanoparticles Capped by Long-Chain Alkyl Carboxylates from Silver Carboxylate and Tertiary Amine

Abstract: Monodispersed silver nanoparticles capped by long-chain alkyl carboxylates were prepared by the reaction of silver carboxylate with tertiary amine at 80 degrees C for 2 h. This approach is a unique, size-controlled synthetic method for the large-scale preparation of silver nanoparticles. Long-chain alkyl carboxylate derived from a precursor acts as a stabilizer to avoid the aggregation of silver nanoparticles and to control particle size. In addition, amine plays an important role both as a reagent to form a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
138
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(145 citation statements)
references
References 45 publications
7
138
0
Order By: Relevance
“…Interestingly, the reducing agents had an apparent effect on the size of Ag NPs because Nakamoto et al reported that the types of amines had negligible effect. 28 They attempted several types of tertiary alkyamines and primary amines. None affected the size and size distribution of the NPs except for n-octylamine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the reducing agents had an apparent effect on the size of Ag NPs because Nakamoto et al reported that the types of amines had negligible effect. 28 They attempted several types of tertiary alkyamines and primary amines. None affected the size and size distribution of the NPs except for n-octylamine.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23][24][25] Nakamoto et al reported the synthesis of Ag NPs from the decomposition of a specially designed coordinated compound. [26][27][28][29] The Ag NPs were prepared by the reduction of Ag(I) carboxylates with a reducing agent, triethylamine, under mild conditions, e.g. 80 o C. 26 The size (from 2.7 nm to 4.4 nm) of the Ag NPs was strongly affected by the alkyl chain length of the carboxylate, while the reducing agent and other reaction conditions had a negligible effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 It has been often reported that Ag nanoparticles have been obtained through the decomposition of Ag(I) complexes in the presence of reductants such as triethylamine. [35][36][37][38] They have also been observed in some other solvents, such as DMSO, CHCl 3 and DMF. Chlorobenzene, with both aromatic and reducing properties, formed a yellowish, clear gel indicating the production of Ag nanoparticles within the gel.…”
mentioning
confidence: 86%